Deconstructing Future AMOC Decline at 26.5°N - Helene Asbjørnsen; Marius Årthun (Geophysical Research Letters)
Abstract The Atlantic Meridional Overturning Circulation (AMOC) is frequently used to diagnose the state of the North Atlantic circulation, but as an integrated quantity the AMOC strength does not necessarily mirror changes in the individual circulation components. Here, we investigate future circulation changes in the subtropical North Atlantic (26.5°N) in CMIP6 models, diagnosing the relationship between the Gulf Stream, Deep Western Boundary Current (DWBC), gyre recirculation, and the integrated AMOC response. Under continued high emissions, we find a multi‐model mean Gulf Stream weakening of 29% (11.2 Sv) and a DWBC weakening of 47% (8.5 Sv) by the end of the century. However, 33% (3.7 Sv) of the Gulf Stream weakening is due to changes in wind stress and therefore not simply a compensating effect for reduced high‐latitude water mass transformation and a weaker DWBC. Our findings have implications for how we understand the dynamics of future North Atlantic circulation changes.